A practical guide to teaching English in the secondary school - Green, Andrew, 1969- (London : Routledge, 2013)
'A Practical Guide to Teaching English in the Secondary School offers straightforward advice, inspiration and support for all training and newly qualified secondary English teachers. Based on the best research and practice available, it offers a wide range of tried and tested strategies and practical activities to ensure success in the secondary classroom. Packed with photocopiable resources and illustrated throughout with examples of good practice and samples of pupils' work, the Practical Guide covers key aspects of English teaching, including: - Effective lesson planning and pupil progress - Getting started with drama - Teaching poetry successfully and enjoyably - Media education and media studies - an introduction to the curriculum and designing schemes of work - Teaching English language - Choosing and using fiction for all ages - English literature at A Level - Opportunities for ICT in English - Planning meaningful assessment. A Practical Guide to Teaching English in the Secondary School is an essential companion to the best selling Learning to Teach English in the Secondary School. Written by expert professionals, it provides detailed examples of theory in practice, enabling you to analyse and reflect on your own teaching in order to ensure pupil learning is maximised. Providing a combination of practical ideas, educational rationales and activities to stimulate personal thought and development, this book explores a wide range of issues pertinent to the teaching and learning of English in the 21st century'--
Introduction / Andrew Green -- Subject knowledge / Andrew Green -- Lesson planning / Liz Ridout -- Teaching writing / Andrew Green -- Drama in English / Rob Smith -- Media in English / Andrew Green -- Teaching language / Ishmael Lewis -- Teaching poetry / Andrew Green -- Teaching reading / Carmel Kellett and Linda Varley -- Teaching English Literature post-16 / Carol Atherton -- Teaching English using ICT.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching (Secondary) -- United Kingdom; Education, Secondary -- Aims and objectives -- United Kingdom; Curriculum planning -- United Kingdom